Enhancing the Biosorption Capacity of Macrocystis Pyrifera: Effects of Acid and Alkali Pretreatments on Recalcitrant Organic Pollutants Removal - Ureta-Zanartu, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The effects of acid and alkali pretreatments on the physicochemical and textural properties of Macrocystis pyrifera were evaluated to assess its potential for removing recalcitrant organic pollutants from aquatic systems. Untreated (UB), acid-pretreated (ACPB), and alkali-pretreated (ALPB) seaweed biomass were characterized using SEM, FTIR-ATR, N2 adsorption–desorption, and potentiometric titrations. Adsorption isotherms and kinetic studies, using methylene blue (MB) as a model pollutant, were conducted to evaluate removal performance. All biosorbents exhibited Langmuir behavior, with maximum adsorption capacities of 333 mg g−1 (UB), 189 mg g−1 (ACPB), and 526 mg g−1 (ALPB). FTIR-ATR and SEM analyses revealed that alkali pretreatment increased the abundance of hydroxyl, carboxylate, and sulfonated functional groups on the seaweed cell walls, along with greater porosity and surface roughness, resulting in enhanced MB adsorption. In contrast, acid pretreatment increased the exposure of carboxylic, amine, and amide functional groups, reducing the electrostatic interactions. The adsorption energy values further supported this, while the intra-particle diffusion model indicated a two-step process involving MB diffusion onto the seaweed surface, followed by diffusion into internal pores. These findings highlight the potential application of Macrocystis pyrifera-based biosorbents in the treatment of wastewater containing recalcitrant organic pollutants. © 2025 by the authors.